Electroweak superpartners scrutinized at the LHC in events with multi-leptons - Iñaki Lara; Daniel E. López-Fogliani; Carlos Muñoz (Physics Letters B, 2019)
We analyze a multi-lepton signal plus missing transverse energy from neutrinos expected at the LHC for a bino-like neutralino as the lightest supersymmetric particle (LSP), when the left sneutrino is the next-to-LSP and hence a suitable source of binos. The discussion is carried out in the framework of the μνSSM, where the presence of R-parity violating (RPV) couplings involving right-handed neutrinos solves the μ problem and can reproduce simultaneously the neutrino data. Left sneutrinos/sleptons are pair-produced at pp collisions decaying to binos, with the latter decaying via RPV to Wℓ or Zν. This signal can be compared with LHC searches for electroweak superpartners through chargino–neutralino production. The reduced cross section of the sneutrino/slepton production in comparison with the one of the latter process, limits the sensitivity of the searches to small sneutrino/slepton masses. Although the resulting compressed spectrum typically evades the aforementioned searches, we show that analyses using recursive jigsaw reconstruction are sensitive to these scenarios. As a by-product, we find that the region of bino masses 110–120 GeV and sneutrino masses 120–140 GeV can give rise to a tri-lepton signal compatible with the local excess recently reported by ATLAS. Keywords: Supersymmetry phenomenology, Supersymmetric standard model, LHC phenomenology